2017
DOI: 10.3390/w9030192
|View full text |Cite
|
Sign up to set email alerts
|

Photoautotrophic Microalgae Screening for Tertiary Treatment of Livestock Wastewater and Bioresource Recovery

Abstract: Photoautotrophic microalgae offer high promise for a tertiary treatment of livestock wastewater owing to their rapid growth and nutrient uptake. To screen better microalga for the tertiary treatment, batch photobioreactor tests were conducted using Chlorella emersonii, Chlorella sorokiniana, and Botryococcus braunii. This study evaluated their specific growth rates, CO 2 utilization rates, and nutrient removal rates to provide appropriate selection guidelines. Based on statistical comparisons, results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The difference in phycoremediation of wastewater by microalgae grown under the same conditions suggests that selecting the right microalgal specie is an important factor to consider when remediating wastewater with microalgae. This is also in agreement with observations by Kim and Kim [29] in their study of phycoremediation potential of tertiary livestock stock wastewater and bioresource recovery.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The difference in phycoremediation of wastewater by microalgae grown under the same conditions suggests that selecting the right microalgal specie is an important factor to consider when remediating wastewater with microalgae. This is also in agreement with observations by Kim and Kim [29] in their study of phycoremediation potential of tertiary livestock stock wastewater and bioresource recovery.…”
Section: Discussionsupporting
confidence: 93%
“…Wastewater samples were collected from the Northern wastewater (29 • 29.122 E) in Durban, KwaZulu-Natal province of South Africa. The treatment plants are amongst the major wastewater treatment plants in the province and utilize the activated sludge treatment system to treat wastewater.…”
Section: Sample Collection and Processingmentioning
confidence: 99%
“…An option to increase the cost-effectiveness is the cultivation of microalgae in wastewater, which is a complex mixture that may serve as a source of nutrients and water [3]. This strategy allows for nutrient recycling with savings in microalgae cultivation costs and, simultaneously contributes to enhancing the sustainability of wastewater treatment [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Kim and Kim [ 6 ] cultivated Chlorella emersonii in CWW from a tertiary treatment mixed with BG-11 culture medium and obtained μ max = 0.61 day −1 and Td = 1.2 days. The growth rate and doubling time in the present study that most approached the values reported by these authors are those obtained in experiment 1 (R1).…”
Section: Resultsmentioning
confidence: 99%